Vertical Paxos and Primary-Backup Replication - Lamport, Leslie; Malkhi, Dahlia; Zhou, Lidong (Microsoft, 2009)
We introduce a class of Paxos algorithms called Vertical Paxos, in which reconfiguration can occur in the middle of reaching agreement on an individual state-machine command. Vertical Paxos algorithms use an auxiliary configuration master that facilitates agreement on reconfiguration. A special case of these algorithms leads to traditional primary-backup protocols. We show how primary-backup systems in current use can be viewed, and shown to be correct, as instances of Vertical Paxos algorithms. This paper came out of much discussion between Malkhi, Zhou, and myself about reconfiguration. Some day, what we did may result in a long paper about state-machine reconfiguration containing these results and others that have not yet been published. The ideas here are related to the original, unpublished version of [151].